2019
DOI: 10.3390/jof5040098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Mitochondrial Pan-Mucorales Marker for the Detection, Identification, Quantification, and Growth Stage Determination of Mucormycetes

Abstract: Mucormycosis infections are infrequent yet aggressive and serious fungal infections. Early diagnosis of mucormycosis and its discrimination from other fungal infections is required for targeted treatment and more favorable patient outcomes. The majority of the molecular assays use 18 S rDNA. In the current study, we aimed to explore the potential of the mitochondrial rnl (encoding for large-subunit-ribosomal-RNA) gene as a novel molecular marker suitable for research and diagnostics. Rnl was evaluated as a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Recent studies have confirmed the value of qPCR in BAL, with regard to earlier diagnosis and better outcomes in cases of pulmonary mucormycosis [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Diagnosismentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies have confirmed the value of qPCR in BAL, with regard to earlier diagnosis and better outcomes in cases of pulmonary mucormycosis [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Diagnosismentioning
confidence: 94%
“…Most of the molecular tests target the 18S ribosomal RNA genes, but also other targets have been investigated. These include the 28S rDNA [ 104 ], the mitochondrial gene rnl [ 105 ], the cytochrome b gene [ 106 ] or the Mucorales-specific CotH gene [ 107 ].…”
Section: Diagnosismentioning
confidence: 99%
“…We were able to detect and quantify genomic DNA of mucormycetes in small quantities of murine organ homogenates (20 mg). The primers were found to be specific for mucormycetes [13].…”
Section: Fungal Load and Dissemination After Inhalative Infection Witmentioning
confidence: 99%
“…They evaluated their method using experimentally infected mice for plasma, urine, and bronchoalveolar lavages as well as urine from patients with proven mucormycosis and concluded that the CotH gene was a promising target for diagnostics in urine samples [14]. Further, Caramalho et al, (2019) tested the mitochondrial rnl gene, which encodes for the large subunit of the rRNA, for diagnostic purposes, using a qPCR + HRM assay [35]. The authors found a 100% rate of correct identification of culture isolates and a relatively high sensitivity for the detection of Mucorales in FFPE samples of 71%.…”
Section: Target Genes and Sequence Databasesmentioning
confidence: 99%
“…The authors found a 100% rate of correct identification of culture isolates and a relatively high sensitivity for the detection of Mucorales in FFPE samples of 71%. Mitochondrial genes are more protected from degradation and are present in higher copy numbers than nuclear DNA, which makes them promising candidates for diagnostic assays [ 35 ]. Finally, the cytochrome b gene was targeted by a probe-based qPCR + HRM Mucorales-specific assay, which was evaluated for culture isolates, fresh tissue, and FFPE tissue, resulting in sensitivities of 100%, 100%, and 56%, respectively [ 36 ].…”
Section: Dna-based Diagnosismentioning
confidence: 99%